2003
DOI: 10.1074/jbc.m211576200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Nuclear Export Signal within the Human T Cell Leukemia Virus Type I Transactivator Protein Tax

Abstract: Human T cell leukemia virus type I (HTLV-I) is the etiologic agent of adult T cell leukemia and HTLV-Iassociated myelopathy/tropical spastic paraparesis. The HTLV-I transactivator protein Tax plays an integral role in the etiology of adult T cell leukemia, as expression of Tax in T lymphocytes has been shown to result in immortalization. In addition, Tax is known to interface with numerous transcription factor families, including activating transcription factor/cAMP response elementbinding protein and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 55 publications
9
107
2
Order By: Relevance
“…These data are correlated with high nuclear/cytoplasmic shuttling activity of Tax (Fig. 6A, third panel from top, lanes 5 and 6) (45). In support of the results of subcellular immunoblot assays, our immunofluorescence assays showed that, in the presence of Tax, p100 exhibited a whole-cell expression pattern (Fig.…”
Section: Both the C-and N-terminal Functional Domains Of P100 Are Esssupporting
confidence: 71%
“…These data are correlated with high nuclear/cytoplasmic shuttling activity of Tax (Fig. 6A, third panel from top, lanes 5 and 6) (45). In support of the results of subcellular immunoblot assays, our immunofluorescence assays showed that, in the presence of Tax, p100 exhibited a whole-cell expression pattern (Fig.…”
Section: Both the C-and N-terminal Functional Domains Of P100 Are Esssupporting
confidence: 71%
“…Interestingly, the two amino acids corresponding to the M22 domain (aa 130-131) (Smith and Greene, 1990) are modified in the Tax3 vs Tax1 protein. The stretch of amino acid that is analogous to the previously reported Nuclear Export Signal of Tax1 (aa 188-202) (Alefantis et al, 2003) also contains several changes, but none of them corresponding to an essential leucine or isoleucine residue. Some changes are also present in the putative Tax3 S CR2-binding sequence (aa 312-319).…”
Section: Resultsmentioning
confidence: 70%
“…Functional domains and potential sites of phosphorylation in Tax. Tax contains a nuclear localization signal (NLS) (13) and a nuclear export signal (NES) (15). Domains for binding CREB, SH3, p300/CBP, IKK␥, LIM, P/CAF, and PDZ are indicated (19,(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, with respect to the regulation of multiple Tax activities, it has been noted that mutation or deletion of individual domains results in a selective loss of function (13). Important domains for Tax function include a nuclear localization signal (13,14), nuclear export signal (15,16), activation specific region (17), two leucine zip-like domains (18,19), and a zinc-finger domain (20). Mutation of a number of individual serine residues in Tax have been shown to alter its ability to trans-activate either CREB or NF-B-responsive promoters (13).…”
mentioning
confidence: 99%